Tetrahydrocannabinol and cannabidiol oromucosal spray in resistant multiple sclerosis spasticity: consistency of response across subgroups from the SAVANT randomized clinical trial. (1st December 2020) - Meuth, Sven G; Henze, Thomas; Essner, Ute; Trompke, Christiane; Vila Silván, Carlos
Abstract: Objective: To determine whether differences in disability status, spasticity severity, and spasticity duration at treatment start in patients with resistant multiple sclerosis (MS) spasticity might influence response to add-on tetrahydrocannabinol:cannabidiol (THC:CBD) oromucosal spray (nabiximols) versus further re-adjustment of optimized first-line antispasticity medication. Methods: Using the database from the Sativex ® as Add-on therapy Vs. further optimized first-line ANTispastics (SAVANT) study, this post hoc analysis evaluated spasticity severity (0-10 numerical rating scale [NRS] scores) and pain severity (0–10 NRS scores) evolution from randomization (baseline) to week 12 (end of double-blind treatment) in defined subgroups: Expanded disability status scale [EDSS] score subgroups (<6 and ≥6); spasticity severity 0-10 NRS score subgroups (4 to ≤6 and >6), and spasticity duration subgroups (<5 and ≥5 years). Results: THC:CBD oromucosal spray (nabiximols) halved mean severity scores for spasticity and pain in all subgroups. Active treatment significantly improved mean spasticity severity scores versus placebo from week 4 onwards in both EDSS subgroups, in the severe spasticity subgroup, and in both spasticity duration subgroups. Active treatment significantly improved mean pain severity scores versus placebo in the ≥6 EDSS subgroup, in the severe spasticity subgroup and in both spasticity duration subgroups. Conclusion: Add-on THC:CBD oromucosal spray (nabiximols) consistently relieves resistant spasticity across subgroups defined by baseline EDSS score, spasticity severity NRS score and spasticity duration. Patients with moderate resistant MS spasticity benefit numerically from treatment; patients with severe resistant spasticity achieve significant therapeutic gains. Spasticity-associated pain often improves similarly in the same subgroups.